Successful remission induction therapy with azacitidine and venetoclax for a treatment-naive elderly patient with ETP/myeloid mixed-phenotype acute leukemia: a case report - Huang, Kaikai; Pang, Yanbin (Frontiers in Oncology, 2025)
BackgroundMixed-phenotype acute leukemia (MPAL) is a rare acute leukemia for which data are currently not available to guide therapy. It has a poor outcome, particularly in elderly patients.Case presentationWe report the successful use of venetoclax/azacitidine as treatment for a treatment-naive elderly patient with early T-cell precursor (ETP)/myeloid MPAL. Initial laboratory studies showed 62% blast cells and 32% lymphocytes on peripheral blood smear. Bone marrow aspiration showed two types of abnormal cell populations. Cytochemical staining showed that myeloperoxidase (MPO) was positive. Immunophenotyping with multicolor flow cytometry analysis showed two distinct populations of blasts with ETP acute lymphoblastic leukemia (ETP-ALL) and myeloid phenotype blasts, respectively. Molecular studies showed no abnormality of the fusion gene transcript. Missense mutation gene was found in genes including DNMT3A, JAK3, and NOTCH1 using next-generation DNA sequencing. Conventional karyotyping of this marrow aspirate revealed 46, XX[10]. She was diagnosed as having MPAL with two distinct blast lineages. Induction therapy was started using venetoclax/azacitidine. The patient developed COVID-19 on the second day of induction therapy. Consequently, the administration of subsequent doses of venetoclax/azacitidine for induction therapy was delayed, and nirmatrelvir/ritonavir was given as therapy for COVID-19. Fortunately, after 5 days of treatment with nirmatrelvir/ritonavir, the patient’s COVID-19 viral load became undetectable (nasopharyngeal swab negative) on 17 January 2023. During induction therapy, the patient was positive for COVID-19 twice but remained asymptomatic. Therefore, the induction treatment was not interrupted. She achieved complete remission with hematological recovery. She spontaneously developed anti-COVID-19 antibodies. The patient continued to receive treatment with venetoclax/azacitidine as planned. At the last follow-up in December 2023, the patient died after 11 months from the initiation of venetoclax/azacitidine because she gave up chemotherapy after 5 months.ConclusionWe report on an elderly patient with MPAL treated with venetoclax combined with azacitidine. This regimen successfully induced complete remission with no adverse side effects, and despite testing positive for COVID-19 multiple times during induction therapy, accompanied by mild dry cough but no radiographic evidence of pneumonia, the patient remained clinically stable.